Radio Repair Management PAE Transmitter Frequency 133.2 Mhz Sibiru-Biru - Muhammad Caesar Akbar; Ludfia Anggi Safitri Sinaga (Yayasan Sinergi Multidimensi Kreatif, 2024)
The use of VHF Air to Ground (VHF A/G) radio equipment as a means of communication between the Air Traffic Controller (ATC) Tower and the aircraft must be guaranteed to be available. To serve the communication needs in the Jakarta Air Traffic Service (JATSC) area, it is necessary to place VHF radios in several locations called VHF Extended Range (VHF-ER). In the VHF-ER system, the information signal from the VHF radio is transmitted through the Very Small Aperture Terminal (VSAT) transmission line. In this report, the problem of TX VHF-ER Radio that cannot be used to communicate is discussed. Where on the Radio there is a menu that affects the running of communication, namely the polarities menu. In this menu, there are values that must be adjusted so that communication can run smoothly, namely 14V, 0V, and -14V. When it cannot be used to communicate, the value on the menu is 14, then it is lowered to -14 while checking the power supply, interconnection and cable jumpers on the serial and LAN ports.